ALTERNATIVE INVESTMENT OPTIONS IN INDIA: A COMPREHENSIVE OVERVIEW - Shyamala Krishnamurthy, Dr. Vanathi Vembar (South Eastern European Journal of Public Health, 2025)
India's investment landscape has undergone significant transformation over the past two decades, with alternative investments emerging as a prominent sector. This paper explores various alternative investment options in India, including real estate, private equity, venture capital, hedge funds, and commodities. We analyze the risks, returns, and regulatory environment surrounding these investment avenues, offering insights into their potential for portfolio diversification and long-term growth. Statistical analysis of performance data provides a quantitative perspective, making the paper a valuable resource for investors, financial advisors, and policymakers.